Association of the body roundness index with chronic diarrhea and chronic constipation: findings based on the National Health and Nutrition Examination Survey 2005–2010 data - Yinda Wang; Fei Chen; Binzhong Zhang; Zhengwei Song (Lipids in Health and Disease)
Abstract Aim The study aimed to explore potential links between long-term digestive issues (specifically diarrhea and constipation) and body roundness index (BRI) in a representative U.S. population sample. Methods This study adopted a design that is cross sectional, drawing on data from the NHANES, gathered from 2005 to 2010 with health information from a total of 11,235 individuals. Persistent bowel movement patterns were categorized based on the BSFS—Bristol Stool Form Scale, while stool types 1 and 2 were designated as indicators of long-term constipation and types 6 and 7 were identified as markers of persistent diarrhea. To assess the relationship between digestive health and the BRI, this study employed weighted logistic regression analysis. To capture and visualize the nuanced interplay between BRI and gastrointestinal patterns, we utilized advanced nonlinear regression methods, specifically restricted cubic spline (RCS) analyses. Additionally, the research compared the efficacy of various physical measurements—including BRI, WC, BMI (body roundness index, waist circumference, and body mass index, respectively)—to determine their respective diagnostic power for chronic diarrhea and constipation through comparative analysis of receiver operating characteristic (ROC) curves. Results After comprehensive adjustment in the final statistical model (Model 3), the BRI demonstrated the statistically significant associations with diarrhea and persistent constipation. RCS analysis further uncovered statistically significant nonlinear positive associations of BRI and with diarrhea (P = 0.005) and constipation (P = 0.037). Further stratified analyses revealed that the relationship between BRI and persistent diarrhea was particularly evident among individuals with diabetes. In contrast, the association between BRI and constipation was stronger in individuals under 60 years of age. ROC analysis indicated that BRI outperformed conventional anthropometric measures (AUC, area under the curve: 0.601). Specifically, BMI resulted in an AUC of 0.569, while WC produced an AUC of 0.572. However, the AUC value of BRI (0.537) was less effective than BMI (0.551) and WC (0.570) in diagnosing constipation. Conclusions BRI is strongly associated with changes in the individual’s bowel habits, particularly in diagnosing chronic diarrhea. This study highlighted the potential significance of maintaining moderate BRI levels to improve bowel health and prevent diarrhea.